2014
DOI: 10.4018/978-1-4666-5982-7.ch004
|View full text |Cite
|
Sign up to set email alerts
|

Examining Middle-School Students' Uses of Diigo Annotations to Engage in Collaborative Argumentative Writing

Abstract: This chapter explores the ways sixth grade students from a linguistically and culturally diverse classroom used Diigo, an online social bookmarking site, to engage in annotation writing focused on the discussion of science ideas within a text. While the use of apps has rapidly increased in schools, there remains little research on the ways annotation writing can be used to support scientific argumentation. Findings from this study indicate that students used the annotation app to pose questions, formulate clai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 30 publications
0
6
0
1
Order By: Relevance
“…Following the same line of thought, some researchers suggested that when implementing similar tools in instructions, teachers should scaffold with active learning strategies, such as raising questions, to better stimulate students' ideas and thinking during discussion (Lin et al, 2019;Sun et al, 2023). Other researchers have recommended that future studies should investigate less examined aspects, such as the teaching of writing in EFL education, to expand the impact of research on social annotation (Castek et al, 2014).…”
Section: Social Annotation Toolsmentioning
confidence: 99%
“…Following the same line of thought, some researchers suggested that when implementing similar tools in instructions, teachers should scaffold with active learning strategies, such as raising questions, to better stimulate students' ideas and thinking during discussion (Lin et al, 2019;Sun et al, 2023). Other researchers have recommended that future studies should investigate less examined aspects, such as the teaching of writing in EFL education, to expand the impact of research on social annotation (Castek et al, 2014).…”
Section: Social Annotation Toolsmentioning
confidence: 99%
“…Among the variety of new technologies that afford language learners' engagement in digital information literacy and reading online are annotation and social bookmarking Web 2.0 tools, such as A.nnotate and Diigo, short for Digest of Internet Information, Groups and Other Stuff (Ruffini, 2011; Thoms & Poole, 2017). Prior research on online annotation programs and language learning and teaching shows that annotation tools help language learners share knowledge, collaborate and interact, develop their higher‐level cognitive abilities (evaluating, analysing, critiquing, and summarizing), and improve their vocabulary and reading proficiency in a second language (L2; Castek et al, 2014; Lu & Deng, 2012; Yang et al, 2011). Some students, however, found other students' annotations about new vocabulary to be disruptive and useless (Hsu et al, 2013).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Lu and Deng found that Diigo enhanced the participants' higher order and critical thinking skills and developed a positive attitude to this social bookmarking tool. Castek, Beach, Cotanch, and Scott's (2014) study on middle school science students' annotations in Diigo revealed that students read texts more actively and used them for a variety of purposes, such as asking questions, requesting evidence from classmates to answer questions, and making judgments about the scientific texts.…”
Section: Technology and L2 Readingmentioning
confidence: 99%